2022
DOI: 10.3390/su14095131
|View full text |Cite|
|
Sign up to set email alerts
|

Tourism Network Attention Variation of Chinese Cities under the COVID-19 Pandemic

Abstract: At the end of 2019, the COVID-19 pandemic broke out globally and had a tremendous impact on tourism development in countries around the world. The rapid shift of tourism from “over-tourism” to “under-tourism”, threatening the future of the global economy and society, has generated considerable interest from academia and the policy community, but the impact of COVID-19 on tourism variation remains untested by empirical evidence. Based on the daily Baidu Index of 247 prefecture-level cities in China from 2018 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…For example, some scholars have used the network attention of websites such as Qunar, Ctrip, and Dianping as data to study the coupling between network attention and scenic attraction [40]. At the same time, scholars have also paid attention to the influencing factors of tourism online attention [41]. Research has found that important factors influencing online attention include economic level, population size, distance, climate, and transportation [42].…”
Section: Network Attentionmentioning
confidence: 99%
“…For example, some scholars have used the network attention of websites such as Qunar, Ctrip, and Dianping as data to study the coupling between network attention and scenic attraction [40]. At the same time, scholars have also paid attention to the influencing factors of tourism online attention [41]. Research has found that important factors influencing online attention include economic level, population size, distance, climate, and transportation [42].…”
Section: Network Attentionmentioning
confidence: 99%
“…Network attention is a statistical standard based on social media and search engine data to assess the popularity of specific keywords, reflecting the degree of user attention towards specific objects [ 1 ]. The application of network attention in the tourism sector also reflects tourists' attitudes towards related tourism elements and phenomena [ 2 ], profoundly influencing tourists' behavior [ 3 , 4 ]. It has been widely used to predict tourism demand and assess the development potential for tourism destinations [ [5] , [6] , [7] , [8] ].…”
Section: Introductionmentioning
confidence: 99%
“…The authors would like to make the following corrections to the published paper [1]. The changes are as follows:…”
mentioning
confidence: 99%